A multi-function wearable radio transceiver device based on radio communication technology. (May 2021) - Wu, Hsin-Te; Chen, Mu-Yen
Abstract: This study proposes a multi-function wearable radio transceiver device based on radio communication technology that utilizes the 2.4 GHz channel, which is open to the public, for communication; the suggested approach aims to support climbers. Each climber is equipped with a wearable device that bears the following functions: (1) radio communication function; users can engage in communication via the radio transceiver; (2) physiological sensor function; the device consistently detects the user's body temperature and heart rate and triggers an alert if any said index shows an anomaly; (3) a one-touch panic button function; when the user presses down the emergency button, the device triggers a distress signal; (4) power-saving and positioning functions. Utilize drones and radio communication technology to conduct search and rescue, the system positions by analyzing the strength of the distress signal, which incorporates a heart rate index that helps to assess the climber's current physiological condition. Highlights: The system is set up on the mountain climber's wearable device, and the main functions include (1) half-duplex communication, which enables voice communication between mountaineering teams and their members, (2) body temperature and heart rate detection, which monitors the climber's physical condition so that if hypothermia or heart rate irregularity occurs, the wearable device will send out a warning, (3) a one-touch panic button on the wearable device that triggers a distress signal to await for help to arrive. Distress signals can be voice messages or textless signals, (4) power-saving and positioning features. The proposed system employs drones that incorporate radio communication features for search and rescue. Graphical abstract: